A new beautiful squeaker frog (Arthroleptidae: Arthroleptis) from West Africa - Rödel, Mark-Oliver; Kouamé, N’goran Germain; Doumbia, Joseph; Sandberger, Laura (Zootaxa, 2011)
A new small Arthroleptis from western Guinea, West Africa, is described. The new species differs from all known congeners by the combination of small size and a peculiar red dorsal colour with irregular large black and small white, yellow or blue spots. The ventral side is almost uniform greyish black with a few, small white spots. Males lack hypertrophied third fingers, digital and inguinal spines. Fingers and toe tips are slightly enlarged. The new species differs in its colour pattern, smaller size, broader toe and finger tips, the lack of hypertrophied third fingers and digital spines in males, and a mean of 4.7% in the investigated part of the mitochondrial 16S rRNA gene to A. aureoli, which is morphologically and genetically the most similar species. Genetic comparisons of the new species with other available Arthroleptis sequences from species found across Africa revealed genetic distances of 16.0–23.4%.